The Impact of Climate Change on International Tourism: Evidence from Egypt - Elsayed, Mona Rabea Abd Elfattah (International Journal of Energy Economics and Policy, 2023)
The tourism industry is one of the most important sectors that contributes to global growth. Climate change can have a significant impact on tourism since it requires appropriate weather conditions and a clean environment. Given the close relationship between climate change and tourism, the current study aims to investigate the impact of climate change on international tourism in Egypt from 1990 to 2020. This study aims to supplement the literature on tourism and environmental quality. The autoregressive distributed lag (ARDL) model used in this study to investigate both short and long-run estimates at the same time. Climate change was measured using changes in precipitation, carbon dioxide emissions, and temperature, with gross capital formation (% of GDP) and arable land (% of land area) serving as control variables. The results show that two climate variables (precipitation rate and temperature) have a positive impact but are not significant in the short and long run-on international tourism revenue. Furthermore, carbon dioxide emissions have a long-term negative impact on international tourism revenues.